2003
DOI: 10.1080/0963818031000087907
|View full text |Cite
|
Sign up to set email alerts
|

ERP systems and management accounting change: opportunities or impacts? A research note

Abstract: Enterprise resource planning (ERP) systems, such as SAP, have become widely used in recent years, especially in large companies. Although a considerable amount has been written about them in the professional accounting and computing literature, somewhat surprisingly comparatively little attention has been given to them in accounting research journals. However, the field studies which are beginning to appear suggest that ERP systems are having only a relatively moderate impact on the character of management acc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

25
368
4
41

Year Published

2009
2009
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 385 publications
(438 citation statements)
references
References 7 publications
25
368
4
41
Order By: Relevance
“…Booth et al 2000;Maccarone, 2000;Granlund and Malmi, 2002;Granlund and Mouritsen, 2003;Caglio, 2003;Hyyon, 2003;Lodh and Gaffikin, 2003;Quattrone and Hopper 2003;Scapens and Jazayeri, 2003] suggests that ERP systems have little impact on management accounting, but that the management accountant is evolving into a business consultant (Caglio 2003;Rom and Rohde 2004). This is consistent with the theoretical stance on the role of the accounting in an events-based system environment as first presented by Denna et al (1993, p. 16) and further developed by Hollander et al (1996, p. 14).…”
Section: Impacts Of Erp Implementations Upon Management Accounting Anmentioning
confidence: 99%
See 1 more Smart Citation
“…Booth et al 2000;Maccarone, 2000;Granlund and Malmi, 2002;Granlund and Mouritsen, 2003;Caglio, 2003;Hyyon, 2003;Lodh and Gaffikin, 2003;Quattrone and Hopper 2003;Scapens and Jazayeri, 2003] suggests that ERP systems have little impact on management accounting, but that the management accountant is evolving into a business consultant (Caglio 2003;Rom and Rohde 2004). This is consistent with the theoretical stance on the role of the accounting in an events-based system environment as first presented by Denna et al (1993, p. 16) and further developed by Hollander et al (1996, p. 14).…”
Section: Impacts Of Erp Implementations Upon Management Accounting Anmentioning
confidence: 99%
“…Booth et al (2000) found similar results, as did Rom and Rohde (2004), who concluded that Strategic Enterprise Management (SEM) systems had a positive impact on management accounting practices whereas ERP systems only had a positive impact on transactional management accounting (e.g., data collection). Scapens and Jazayeri (2003) found that under ERP there was no fundamental change in the nature of management accounting information. However, there were changes in the role of management accountants compared with those in traditional accounting environments:…”
Section: Impacts Of Erp Implementations Upon Management Accounting Anmentioning
confidence: 99%
“…problematyki wykorzystania systemów do obliczania finansowych i niefinansowych wskaźników pomiaru dokonań [Spathis, Constantinides 2004], określenia, czy i jaki wpływ wywiera wdrożenie zintegrowanego systemu na stosowany system rachunkowości zarządczej [Scapens, Jazayeri 2003], czy jaki wpływ ma wdrożenie ERP na postrzeganie roli specjalisty rachunkowości zarządczej [O'Mahony, Doran 2008]. 4) Badania dotyczące wsparcia przez systemy ERP implementacji metod rachunkowości zarządczej w jednostkach sektora publicznego.…”
Section: Zastosowanie Rachunkowość Zarządczej W Jednostkach Sektora Punclassified
“…Researchers are increasingly interested in issues arising from the evolution in the roles and functions of management accounting specialists, seeking also to establish where the changes come from (in Poland Sobańska, 2003;Sobańska, Wnuk 2000;Szychta 2002, etc. ;and abroad Burns, Scapens, 2000;Scapens et al 2003).…”
Section: Controller's Role and Functions In An Enterprisementioning
confidence: 99%